Efektivitas Pembiayaan Murabahah Dalam Pengentasan Kemiskinan Di Aceh - Riza, Akmal; Kamal, Zikrul (Fakultas Ekonomi dan Bisnis Islam, Universitas Islam Negeri Ar-Raniry Banda Aceh, 2021)
The problem of poverty in Aceh, with various factors, has made Aceh the poorest region in Sumatra in 2021. One of the efforts to overcome it is by developing the MSME sector. Therefore, the existence of financing at Bank Aceh Syariah is expected to be able to effectively overcome these problems. This study aims to determine the effectiveness of murabahah financing for Micro, Small, and Medium Enterprises in Aceh in poverty alleviation efforts, specifically for the City of Banda Aceh. The method used in this research is qualitative with a descriptive approach. The data sources used were primary and secondary with the techniques of observation, interviews, and documentation studies The results showed that the murabahah financing at PT. Bank Aceh Syariah Operational Headquarters for MSMEs is effective in poverty alleviation efforts, it can be seen that after receiving financing, MSMEs are able to increase income, develop businesses, and create jobs.